The Effectiveness of Instagram Accounts @lpmdinamika as a Campus Press Media - Windy Sakila Nazwa; Andini Nur Bahri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Instagram is one of the communication media that now has an audio-visual style as an additional tool for the campus press in spreading news. As a campus press that is an extension of information to the public, it must take an accurate, precise, and balanced dissemination approach to its targets. Through its visuals and interactive features, LPM Dinamika uses it to interact with its followers. The purpose of this study is to examine the level of effectiveness of @lpmdinamika Instagram accounts as a campus press media in disseminating news. This is based on the ease of access that can be done anywhere and is relevant to daily activities. This study applied a descriptive quantitative research method by distributing questionnaires to 13,100 Instagram followers @lpmdinamika. The research instrument was compiled based on the Likert scale and tested for validity and reliability. The sample size obtained was 100 respondents with a percentage of 73% women and 27% men. Of the 17 statements with an effectiveness rate of 84%, they were in the category of highly effective. Effectiveness is measured through four main indicators, access to information, credibility, quality of information presentation and user satisfaction. The Instagram account @lpmdinamika has made efforts to disseminate effective information judging from the trust of followers in the news by LPM Dinamika. These findings show that @lpmdinamika successfully carried out its role as a campus press medium that not only conveys information but also builds engagement with audiences.